Capitalism and Christianity, American Style - Henry, Caleb (A journal of church and state, 2009)
Over the past several decades, William Connolly has developed a political theory rooted in changing identity and time. These changes suggest that no argument is truly objective. Since faith is required for all political positions, public discourse should be inhabited by those who admit the contestability of their beliefs and maintain an “agonistic respect” for other beliefs. In his latest book, Connolly turns this analysis from academic epistemological hypocrisy to the “evangelical-capitalist resonance machine.”, Connolly's capitalism has no inherent end. It depends upon a faith in the future, which evangelical Christianity, as epitomized by George Gilder, has provided.